2010
DOI: 10.1111/j.1365-2486.2010.02351.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduced N cycling in response to elevated CO2, warming, and drought in a Danish heathland: Synthesizing results of the CLIMAITE project after two years of treatments

Abstract: Field-scale experiments simulating realistic future climate scenarios are important tools for investigating the effects of current and future climate changes on ecosystem functioning and biogeochemical cycling. We exposed a seminatural Danish heathland ecosystem to elevated atmospheric carbon dioxide (CO 2 ), warming, and extended summer drought in all combinations. Here, we report on the short-term responses of the nitrogen (N) cycle after 2 years of treatments. Elevated CO 2 significantly affected abovegroun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
196
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 236 publications
(223 citation statements)
references
References 75 publications
10
196
6
Order By: Relevance
“…The site had a relatively low atmospheric N bulk deposition of 1.35 AE 0.04 g N m -2 year -1 in 2007 (Larsen et al 2011).…”
Section: Site Descriptionmentioning
confidence: 99%
See 2 more Smart Citations
“…The site had a relatively low atmospheric N bulk deposition of 1.35 AE 0.04 g N m -2 year -1 in 2007 (Larsen et al 2011).…”
Section: Site Descriptionmentioning
confidence: 99%
“…The treatments were initiated in October 2005. See Mikkelsen et al (2008) and Larsen et al (2011) for further details of the experimental design and set-up. Fig.…”
Section: Experimental Manipulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Climatic influences on the strength of N deposition relationships have also been identified in modeling studies by Britton et al (2001) as well as in previous surveys of lowland and upland heathlands (Jones and Power 2012;Southon et al 2013), although rainfall, rather than temperature, was found to be important in previous studies. Temperature has a strong influence on vegetation productivity (Larsen et al 2011) and will also affect soil microbial activity (Selsted et al 2012) and thus rates of organic matter turnover and nutrient cycling within soils. A positive effect of higher temperatures on Calluna shoot growth has been shown in a gradient study of heathland vegetation in northern Europe (Prieto et al 2009) and also indirectly in an altitudinal gradient study by Hicks et al (2000).…”
Section: Effects Of Climate On Relationships With N Depositionmentioning
confidence: 99%
“…Soil nitrification rates are sensitive to warming (Larsen et al 2011, Ma et al 2011) and changes in precipitation or soil moisture (Lamersdorf et al 1998, Emmett et al 2004; however, the mechanisms underlying these changes are poorly understood. Nitrification influences soil ammov www.esajournals.org nium (NH 4 þ ) and nitrate (NO 3 À ) content, NO 3 À leaching from the soil, and denitrification, which results in the production of nitrous oxide (N 2 O).…”
Section: Introductionmentioning
confidence: 99%